Anti-Hyperglycemic Agents in the Adjuvant Treatment of Sepsis: Improving Intestinal Barrier Function - Wang YF; Li JW; Wang DP; Jin K; Hui JJ; Xu HY (Dove Medical Press, 2022)
Yi-Feng Wang, Jia-Wei Li, Da-Peng Wang, Ke Jin, Jiao-Jie Hui, Hong-Yang Xu Department of Critical Care Medicine, The Affiliated Wuxi People's Hospital of Nanjing Medical University, Wuxi, Jiangsu, People's Republic of ChinaCorrespondence: Jiao-Jie Hui; Hong-Yang Xu, Email huijiaojie15@163.com; xhy1912@aliyun.comAbstract: Intestinal barrier injury and hyperglycemia are common in patients with sepsis. Bacteria translocation and systemic inflammatory response caused by intestinal barrier injury play a significant role in sepsis occurrence and deterioration, while hyperglycemia is linked to adverse outcomes in sepsis. Previous studies have shown that hyperglycemia is an independent risk factor for intestinal barrier injury. Concurrently, increasing evidence has indicated that some anti-hyperglycemic agents not only improve intestinal barrier function but are also beneficial in managing sepsis-induced organ dysfunction. Therefore, we assume that these agents can block or reduce the severity of sepsis by improving intestinal barrier function. Accordingly, we explicated the connection between sepsis, intestinal barrier, and hyperglycemia, overviewed the evidence on improving intestinal barrier function and alleviating sepsis-induced organ dysfunction by anti-hyperglycemic agents (eg, metformin, peroxisome proliferators activated receptor-γ agonists, berberine, and curcumin), and summarized some common characteristics of these agents to provide a new perspective in the adjuvant treatment of sepsis.Keywords: sepsis, sepsis-induced organ dysfunction, intestinal barrier, anti-hyperglycemic agents